Characterization of Bank Lending Requirements for Farmers in Zimbabwe - Ropafadzo, Chigunhah Blessing; Ezekia, Svotwa; Gerald, Munyoro; Joseph, Mabvure Tendai; Ignatius, Govere (Asian Journal of Agriculture and Rural Development, 2020)
Bank credit availability is vital for enhancing farm productivity, income, and farmer livelihoods. This study sought to characterize the lending requirements considered by commercial banks when lending to farmers in Zimbabwe. Primary data were collected from a cross-section of 12 registered commercial banks. Relative Importance Index (RII) and Thematic analysis analysed data. High importance lending requirements that were always considered by all commercial banks when lending to farmers included credit history, productive farm assets, business registration, loan purpose, amount, and repayment source. Agricultural production skills, age, business plans, financial statements, social reputation, and project insurance were also mandatory in the majority of the commercial banks. High to medium importance lending requirements included extension support, business management skills, bank account ownership, own contribution, and personal savings. Medium importance requirements included formal basic education, alternative income, and freehold land ownership. Therefore, besides the widely documented collateral, local commercial banks also considered several other requirements when lending to farmers. Government policy should go beyond solving the collateral issue but benchmark its policies to other bank lending requirements. Farmers should also pursue personal development programs in agricultural production, business, and financial management. They should also invest in off-farm assets to ensure collateral availability.